Germination of Expired Spinach (Amaranthus hybridus L.) Seeds with Various Coconut Water (Cocos nucifera L.) Concentrations - Nur Malinda; Elvi Rusmiyanto Pancaning Wardoyo; Dwi Gusmalawati (Universitas Islam Raden Rahmat, Malang, 2026)
Spinach (Amaranthus hybridus L.) productivity in Indonesia declined from 170,688 tons in 2023 to 168,400 tons in 2024, a decrease partly attributed to the use of expired seeds with reduced physiological viability. Coconut water (Cocos nucifera L.), which contains auxin and cytokinin, has potential as a natural priming agent to restore the germination capacity of expired seeds, yet its effect at different concentrations on expired spinach seeds using the top-of-paper method has not been established. This study aimed to determine the effect of various coconut water concentrations on the germination of expired spinach seeds. A Completely Randomized Design (CRD) with five treatmentsK0 (control/distilled water), K1 (25%), K2 (50%), K3 (75%), and K4 (100% coconut water)was applied, each replicated five times, and data were analyzed using ANOVA followed by Duncan's Multiple Range Test (DMRT). Coconut water soaking significantly increased germination percentage and germination ability, and significantly reduced abnormal sprouts and dead seeds (p < 0.05). The highest germination percentage (96.8%) and germination ability (92%) were both recorded at 75% coconut water concentration (K3), statistically comparable to 50% (K2) and 100% (K4). The control treatment (K0) produced the highest abnormal sprouts (8.8%) and dead seeds (15.2%), while the 25% concentration (K1) gave the fastest average germination time (2.04 days). These findings indicate that soaking in 50–75% coconut water for 6 hours is an effective, low-cost priming method for restoring the viability of expired spinach seeds and offers a practical recommendation for small-scale seed quality improvement.